Brain organoids for addressing COVID-19 challenge - Yu, Jin; Wang, Kailun; Zheng, Dalin (Frontiers in Neuroscience, 2022)
COVID-19 is a systemic disease involving multiple organs, and clinically, patients have symptoms of neurological damage to varying degrees. However, we do not have a clear understanding of the relationship between neurological manifestations and viral infection due to the limitations of current in vitro study models. Brain organoids, formed by the differentiation of stem cells under 3D culture conditions, can mimic the structure of tiny cell clusters with neurodevelopmental features in different patients. The paper reviewed the history of brain organoids development, the study of the mechanism of viral infection, the inflammatory response associated with neurological damage, the detection of antiviral drugs, and combined microarray technology to affirm the status of the brain organoid models in the study of COVID-19. In addition, our study continuously improved the model in combination with emerging technologies, to lay a theoretical foundation for clinical application and academic research.